G295(P) Pedestrian deaths in irish children – potential for prevention. (27th April 2015) - Hamilton, K; Macken, WL; McGarvey, C; Matthews, T; Nicholson, AJ
Abstract : Aims: To examine the characteristics of child pedestrian fatalities in the Republic of Ireland using the National Paediatric Mortality Register database to provide an evidence base for preventative action. Method: All child fatalities recorded on the National Paediatric Mortality Database from 1st January 2006 to 31st December 2011 were retrospectively reviewed and all road traffic related deaths were examined to identify pedestrian deaths. Passenger and cyclist deaths were excluded. Coroner's autopsy reports and death registration data were reviewed and deaths were categorised as either traffic related or non-traffic related. Deprivation scores were assigned using The Pobal Haase-Pratshke Deprivation Index. Results: There were 45 child pedestrian fatalities identified in the six year period examined. Traffic related deaths accounted for 58% vs. 42% non-traffic related. Analysis of the deaths showed there was a male preponderance. Those with a deprivation index score of "marginally below average" accounted for the majority (53%) of deaths. There was a weekend trend and an evening and summer peak. The highest proportion of deaths occurred in the 1–4 year age group (53%), with 28% due to low speed vehicle rollovers involving the vehicle in a reversing manoeuvre, mainly occurring in residential driveways. Conclusion: Child pedestrian fatalities are highly preventable through the modification of risk factors including behavioural, social and environmental. Most of the effort in preventing child pedestrian injuries in Ireland has focused on education of children. An area which receives little focus is non-traffic related deaths. These tragic deaths mainly involve young children/toddlers who are small in stature but independently mobile and lack the concept of personal safety. Preventative action needs to be addressed in this area.